An Omnidirectional Encircled Deployable Polyhedral Gripper for Contactless Delicate Midwater Creatures Sampling. Issue 8 (7th December 2022) - Xia, Qingchao; Xu, Linghui; Liu, Chen; Yang, Yue; Chen, Yuting; Zhang, Sheng; Yang, Canjun
Abstract : In marine biological sampling, the noncontact polyhedral gripper is initially developed for the purpose of capturing brittle animals and delicate soft‐bodied organisms. However, the auxiliary driving rods of earlier polyhedral grippers make their structure complex, and the unidirectional surrounding capture process makes it simple to generate water flow with less capture effect. Herein, an origami polyhedral gripper for midwater sampling is introduced, along with its fabrication, analysis, material selection, and size parameter calculation process. The capture process is designed to be omnidirectional surrounding; therefore, the generated water flow can be reduced. And the whole mechanism is bi‐stable and only needs one actuator to operate. Capture experiments on pet fish with fragile tails were conducted on a remotely operated vehicle (ROV) and on simply constructing artificial arms to prove its feasibility and high adaptability. Overall, the unit mechanism of this gripper is analyzed using the Screw theory to show how it has a bistate feature. And using the same origami‐structural unit, additional foldable polyhedral structures with the same folding modes are also introduced. Abstract : Herein, a bi‐stable origami polyhedral gripper for midwater sampling is introduced, along with its fabrication, analysis, material selection, and size parameter calculation process. The capture process is designed to be omnidirectional surrounding; therefore, the generated water flow can be reduced. Capture experiments on pet fish with fragile tails prove its feasibility and high adaptability.